THE RELATIONSHIP BETWEEN STIFFNESS LOSSES AND LOSSES IN BEARINGS OF ROPE BLOCKS - Bohomaz, V. M.; Bondarenko, L. M.; Ocheretniuk, M. V.; Tkachov, O. O. (Science and Transport Progress, 2017)
Purpose. To determine the efficiency of rope blocks, it is necessary to determine the stiffness coefficient of the ropes of blocks, taking into account the classification group of the mechanism and the wrapping angle of a block by a rope. At this one should use well-tested values of the efficiency coefficients of the rope blocks, taking into account the wrapping angle of a block by a rope and the analytically found friction coefficients of the rolling bearings given to the trunnion. Methodology. The work presents the analytical method of determining the coefficient of bearing resistance of the block when it is rotated by both the inner and outer cages, as well as the design scheme of the bearing of the block. Findings. The analysis of the lubrication method effect, the operating mode of the mechanism and the wrapping angle of a block by a rope on losses in bearings was carried out for rope blocks. The corresponding comparative tables of losses are given. Analysis of the obtained calculation results allows us to establish: 1) the main resistance affecting the cable blocks efficiency is the resistance in bearings; 2) the second largest component is the stiffness losses, depending on the operating mode, the wrapping angle of a block by a rope, the type of bearing lubrication; 3) the block efficiency when rotating the inner cage is higher than rotating the outer one by about 3% with thick lubrication and 1M mode; 4) in the sequential location of assemblies with a rolling bearing, it is necessary to strive for the design of the assembly in which the inner cage rotates; 5) with the number of blocks up to 5, one can use the recommended definitions of block bearings in the literature with an error in the efficiency value of up to 10%. Originality. The authors obtained values of resistances in the rolling bearings of the rope blocks and stiffness losses due to the girth of the block by the rope. In this case, dependences were used to determine the coefficient of rolling friction, obtained using the Hertz analytic dependences on determination of contact stresses and deformations, as well as the experimental values of the coefficient of rolling friction for the blocks. Practical value. The resistance values obtained by the authors can be used for refined calculations of the mechanisms of machines.